(3TQM bUjOI GdfGHZI GdPHjGfi (B( (3GdOGdjg (B)s - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s ((3YHO GdHGbi HQSe GdCejQ RGO eMehO NGf s)
(3ChdgG (B:s
(3jG OGQ ejI HGdYdjGA aGdSfO CbhJ hWGd YdjgG SGda GdCHO s
(3BNQgG (B:s
(3jbhd Pi gfO hPh gfO hJGgfO hJi gfO hPi YPQ hYRQg hGMO hGdeYfi Cf GdbUjOg YPQ Ci PGJ YPQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HBNQ UaMGJgG JYbjHIs
(3fSNI NGeSgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs